Structural and Molecular Properties of Insect Type II Motor Axon Terminals - Stocker, Bettina; Bochow, Christina; Damrau, Christine; Mathejczyk, Thomas; Wolfenberg, Heike; Colomb, Julien; Weber, Claudia; Ramesh, Niraja; Duch, Carsten; Biserova, Natalia M.; Sigrist, Stephan; Pflüger, Hans-Joachim (Frontiers in Systems Neuroscience, 2018)
A comparison between the axon terminals of octopaminergic efferent dorsal or ventral unpaired median neurons in either desert locusts (Schistocerca gregaria) or fruit flies (Drosophila melanogaster) across skeletal muscles reveals many similarities. In both species the octopaminergic axon forms beaded fibers where the boutons or varicosities form type II terminals in contrast to the neuromuscular junction or type I terminals. These type II terminals are immunopositive for both tyramine and octopamine and, in contrast to the type I terminals, which possess clear synaptic vesicles, only consist of dense core vesicles. These dense core vesicles contain octopamine as shown by immunogold methods. With respect to the cytomatrix and active zone peptides the type II terminals exhibit active zone-like accumulations of the scaffold protein Bruchpilot (BRP) only sparsely in contrast to the many accumulations of BRP identifying active zones of neuromuscular junction type I terminals. In the fruit fly larva marked dynamic changes of octopaminergic fibers have been reported after short starvation which not only affects the formation of new branches (“synaptopods”) but also affects the type I terminals or neuromuscular junctions via octopamine-signaling (Koon et al., 2011). Our starvation experiments of Drosophila-larvae revealed a time-dependency of the formation of additional branches. Whereas after two hours of starvation we find a decrease in “synaptopods”, the increase is significant after six hours of starvation. In addition, we provide evidence that the release of octopamine from dendritic and/or axonal type II terminals uses a similar synaptic machinery to glutamate release from type I terminals of excitatory motor neurons. Indeed, blocking this canonical synaptic release machinery via RNAi induced downregulation of bruchpilot in neurons with type II terminals leads to flight performance deficits similar to those observed for octopamine mutants or flies lacking this class of neurons (Brembs et al., 2007).